Gas-fired CCHP Distributed Energy System and Its Application for Hospital Buildings in Sichuan Province - Tianyu NIU; Jinhui YU (发电技术)
Gas-fired combined cooling, heating and power (CCHP) distributed energy system has made certain progress in China. However, because of unreasonable system design scale and configuration compared with demand, the CCHP system has low operating efficiency, poor economy, unsatisfactory operation effect, and even some of the CCHP systems have been shut down. Taking a middle first-class hospital in Sichuan province as an example, by analyzing current hospital's cooling, heating and power loads on typical day, the cooling, heating and power loads in the newly built hospital branch were projected, and the installed scale and system configuration of CCHP system were specifically determined to realize the economical and efficient operation of CCHP system. Compared with the traditional energy supply system, the rationality of CCHP system in hospital was analyzed from three aspects including economic benefit, energy utilization efficiency and environmental benefit.